(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: The purpose of this study is to present Mónika Nogel’s monograph with the aim of making the potential readership aware of its main values. Methodology: The article was prepared based on the analysis of the monograph described. Findings: The presented monograph analyzes the current issues of expert activity with scientific precision, and can also help the daily work of experts and legal practitioners working with expert opinions. Value: The paper presents review and evaluation of the monograph , Current Challenges of Expert Evidence – Handbook for Experts and Lawyers”, writen by Mónika Nogel. The book was published in 2020.